Integrated Application of Thiourea and Biochar Improves Maize Growth, Antioxidant Activity and Reduces Cadmium Bioavailability in Cadmium-Contaminated Soil - Haider, Fasih Ullah; Virk, Ahmad Latif; Rehmani, Muhammad Ishaq Asif; Skalicky, Milan; Ata-ul-Karim, Syed Tahir; Ahmad, Naeem; Soufan, Walid; Brestic, Marian; Sabagh, Ayman E. L.; Liqun, Cai (Frontiers in Plant Science, 2022)
Cadmium (Cd) contamination of croplands jeopardizes sustainable crop production and human health. However, curtailing Cd transfer and mobility in the rhizosphere-plant system are challenging. Sole application of biochar (BC) and thiourea (TU) has been reported to restrain Cd-toxicity and uptake in plants. However, the combined application of BC and TU in mitigating the injurious effects of Cd on plants has not been thoroughly investigated. Therefore, this study attempted to explore the integrated effects of three maize stalk BC application rates[B0 (0% w/w), B1 (2.5% w/w), B2 (5% w/w)] and three TU foliar application rates [T0 (0 mg L-1), T1 (600 mg L-1), T2 (1200 mg L-1)] in remediating the negative effects of Cd on maize growth, development, and physiology. Results demonstrated that Cd concentration in soil inhibited plant growth by reducing leaf area, photosynthesis activity, and enhanced oxidative stress in maize. Nevertheless, BC and TU application in combination (B2T2) improves the fresh biomass, shoot height, leaf area, and photosynthesis rate of maize plants by 26.93, 41.54, 36.30, and 15.46% respectively as compared to control (B0T0). Additionally, the oxidative stress [malondialdehyde (MDA), hydrogen peroxide (H2O2), and electrolyte leakage (EL)] were minimized by 25.90, 19.98, and 20.96%, respectively under B2T2 as compared to B0T0. The antioxidant enzymatic activities (superoxide dismutase (SOD) and catalase (CAT)) were 81.27 and 58.50% higher in B2T2 than those under B0T0. Besides, the shoot and root Cd concentration were decreased by 41.56 and 49.36%, respectively under B2T2 as compared with B0T0. The application of BC and TU in combination has the potential for improving maize growth on Cd-contaminated soil by reducing Cd contents in plant organs (shoot and roots).